Sustainable practices on waste resulting from the production rice - Halberstadt, Karin Fernanda; Silva, Vanessa Almeida Da; Santos, Marindia Brachak dos; Scherer, Flavia Luciane; Carpes, Aletéia De Moura; Oliveira, Maria Carolina Serpa Fagundes de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The search for an orientation geared to social, environmental and government interests through new and alternative practices have been shown to be essential for organizations that wish to develop themselves sustainably and compete in the global market. Therefore, this study aims to analyze the sustainable disposal of waste arising from the production process of an agribusiness rice in the Rio Grande South Central Region, by means of reverse logistics and other sustainable practices. The methodological designs featuring research as exploratory and descriptive, qualitative approach and utilizes the case study method. The main results showed that economic practices are restricted and are related to sustainability as a focus on quality. With respect to environmental issues it was found that the company performs some simple environmental practices. Now when it comes to social issues, the company signaled worry about the society in which it operates. The researched company produces a wide variety of waste arising from the production process, so the application of reverse logistics has contributed to the proper disposal of these wastes, which have high power of reuse and reprocessing that can create value and competitive organization.